Challenges in adopting open innovation strategies in SMEs : an exploratory study in Portugal - Rahman, Md. Hakikur (2013)
Researches indicate that adoption of open innovation strategies in the entrepreneurships offers a promising way to face the ever increasing challenges due to globalization of entrepreneurships. However, in spite of abundance of researches, practices and case studies on adoption of open innovation strategies in relatively larger firms or corporate houses, studies are rare in the other sector of the entrepreneurships, which is popularly known as the small and medium scale enterprises (SMEs). This study has tried to find out the parameters of challenges that are being faced by the SMEs. A questionnaire has been placed on the Surveymonkey and a few selected companies were approached to participate in the web based survey. Due to the limitation of finding a larger contact list, this paper discusses about the findings of the completed survey, which is being termed as the pilot one. The findings are being discussed within the texts and it is expected that a new survey will start soon with a list containing larger number of companies.